Rebranding of street markets: a design driven approach - Rochin Demong, Nur Atiqah; Kassim, Erne Suzila; Mohamad Yunus, Noorain; Shahrom, Melissa; Abdul Kader Jailani, Sri Fatiany (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
The street market, including the night and farmers’ market, is considered as a less formalized economic activity that operates as part of the coping strategies in communities caught by the domestic response to changes in the global economy. While it is considered as the bottom of the retail pyramid, studies on street markets have found quite a substantial number of advantages that strengthen human and social interactions. Low prices and the possibility of finding deals, and a melting pot for people’s diversity and culture have become the street market essence. However, the liberation of sub-scale retail sector has somehow affected the consumer’s acceptance of the market. Low prices and better-quality products are the retailers’ competitive advantages, while cleanliness, prices do not standardize, and poor services are tarnishing the market’s image. Therefore, it raises the question of how the street markets can regain their competitive advantage and survive in the industry, given the intense competition from the retailers. Malaysian NKEA was introduced to create a balance in equipping the street markets with the modernize transformation in its distribution and operation. In addition, recently TN50 was also launched to further transform and modernize the street market image. However, the action and the development related to the achievement are yet to be well strategized. Hence, it is critical to rebrand the street market into a modern and informative culture. To address the issue, we propose to develop a street market app that will boost users’ experience and later improve their acceptance by using the design driven approach. As IT has become the lifestyle, it is vital that street markets remain savvy, even in digital form, and responsive to consumers’ needs